2021
DOI: 10.3390/polym13172945
|View full text |Cite
|
Sign up to set email alerts
|

Reaction-Induced Phase Separation and Morphology Evolution of Benzoxazine/Epoxy/Imidazole Ternary Blends

Abstract: Introducing multiphase structures into benzoxazine (BOZ)/epoxy resins (ER) blends via reaction-induced phase separation has proved to be promising strategy for improving their toughness. However, due to the limited contrast between two phases, little information is known about the phase morphological evolutions, a fundamental but vital issue to rational design and preparation of blends with different phase morphologies in a controllable manner. Here we addressed this problem by amplifying the difference of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…The chemical distribution is consistent with the blend with A-GNP, indicating that the phase structure could be constructed without the introduction of A-GNP, while the incorporation of A-GNP highlights the phase structure constructed in this epoxy blend, enabling the separated phases to be observed without the necessity of an etching process, which is normally the method used to study the phase morphology of the phaseseparated TS/TS blend. 21,28 With the combination of the chemical mapping on both blends, it could be confirmed that the A-GNPs were selectively located in the domain constructed by the AEPIP-epoxy building blocks during the curing process.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The chemical distribution is consistent with the blend with A-GNP, indicating that the phase structure could be constructed without the introduction of A-GNP, while the incorporation of A-GNP highlights the phase structure constructed in this epoxy blend, enabling the separated phases to be observed without the necessity of an etching process, which is normally the method used to study the phase morphology of the phaseseparated TS/TS blend. 21,28 With the combination of the chemical mapping on both blends, it could be confirmed that the A-GNPs were selectively located in the domain constructed by the AEPIP-epoxy building blocks during the curing process.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…As shown in Figure 4d, the contrast between the two phases is ambiguous and the extent of phase separation is too low to be detected by the optical images, which is one of the main obstacles impeding the investigation of the phase behavior of TS/TS blended systems. 21 However, the chemical difference is clearly evident in the chemical maps shown in Figure 5e,f. The chemical distribution is consistent with the blend with A-GNP, indicating that the phase structure could be constructed without the introduction of A-GNP, while the incorporation of A-GNP highlights the phase structure constructed in this epoxy blend, enabling the separated phases to be observed without the necessity of an etching process, which is normally the method used to study the phase morphology of the phaseseparated TS/TS blend.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 3 more Smart Citations